G279(P) Rsv prevalence in infants admitted with bronchiolitis across central kenya; a prospective study during global links placement. (12th March 2018) - Le Geyt, J; Hauck, S; Lee, M; Mackintosh, J; Slater, J; Razon, D; Williams, B
Abstract : Background: Acute respiratory infections (ARI) continue to be a leading cause of under-five mortality in the developing world. Distinguishing between bacterial and viral causes can be challenging, and although the majority are likely to be viral, most are treated as bacterial pneumonia. In Kenya, the prevalence of Respiratory Syncytial Virus (RSV) in previous, single-centre studies have varied greatly. Aims: To determine the prevalence of RSV infection in children admitted with ARI to five hospitals in Kenya, and to analyse if there were any significant associations between RSV infection and clinical signs. Methods: A prospective cross-sectional prevalence study was conducted in five different district hospitals across central and highland Kenya from April to June 2015. Lead paediatricians were Global Links volunteers (RCPCH). Children admitted who fitted the WHO criteria for bronchiolitis had bedside RSV immunochromatography testing, and data collected about their demographics, symtpoms and signs. Results: 234 participants were enrolled across the five hospitals. The overall RSV positive rate was 8.1%, although this varied between the sites. The average age of RSV positive cases was 3.9 months and RSV negative 9.2 months. Difficulty in feeding was the only clinical sign significantly associated with an RSV positive result. Conclusion: This is the first published study to look at the RSV prevalence rate in children admitted with ARIs in these areas across central and highland Kenya. The RSV rate of 8.1% is much lower than that previously reported in other parts of Kenya. Much further work is needed to better understand the viral aetiology of paediatric ARIs across the different areas of Kenya to be able to make evidenced based decisions for future public health programs and clinical guidelines.